2018
DOI: 10.1038/s41431-017-0079-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel MAP3K7 splice mutation causes cardiospondylocarpofacial syndrome with features of hereditary connective tissue disorder

Abstract: Heterozygous variants in MAP3K7, encoding the transforming growth factor-β-activated kinase 1 (TAK1), are associated with the ultrarare cardiospondylocarpofacial syndrome (CSCFS). Specific gain-of-function variants in the same gene cause the allelic frontometaphyseal dysplasia type 2. Phenotypic series of frontometaphyseal dysplasia also comprise variants in FLNA (type 1) and two patients with a heterozygous variant in TAB2 (type 3). We report on a 7-year-old girl with CSCFS due to the novel heterozygous c.737… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 17 publications
4
28
1
Order By: Relevance
“…This case highpoints that while molecular diagnosis in patients with a full-blown phenotype is mainly confirmatory, in those with an incomplete presentation it turns out to be fundamental, since these individuals might not be diagnosed or even be misdiagnosed. Indeed, considering the clinical overlap not only between the different EDS subtypes but also with other HCTDs [1,9,28,30,32,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], differential diagnosis is not always forthright. Differential diagnosis includes the molecularly unsolved hEDS that shares with cEDS gJHM and more than a few (muco) cutaneous signs; however, hEDS patients usually show a lower degree of scarring and skin hyperextensibility and much more striking gJHM complications [1,7,28,29,50].…”
Section: Discussionmentioning
confidence: 99%
“…This case highpoints that while molecular diagnosis in patients with a full-blown phenotype is mainly confirmatory, in those with an incomplete presentation it turns out to be fundamental, since these individuals might not be diagnosed or even be misdiagnosed. Indeed, considering the clinical overlap not only between the different EDS subtypes but also with other HCTDs [1,9,28,30,32,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], differential diagnosis is not always forthright. Differential diagnosis includes the molecularly unsolved hEDS that shares with cEDS gJHM and more than a few (muco) cutaneous signs; however, hEDS patients usually show a lower degree of scarring and skin hyperextensibility and much more striking gJHM complications [1,7,28,29,50].…”
Section: Discussionmentioning
confidence: 99%
“…The novel MAP3K7 variant seen in Patient 1 is close to two previously recorded mutations associated with CSCFS, p.Arg44_Gly45del and p.Val50del, all within the kinase domain of the protein (Le Goff et al 2016). All but one of the recorded variants in patients with FMD2 or CSCFS have been in the kinase domain (Morlino et al 2018); however, it is important to note that a single missense variant in the C-teriminus of MAP3K7, p.Pro512Leu, is reponsible for FMD2 in mutliple unrelated individuals who typically have a more severe presentation than those with variants in the kinase domain (Wade et al 2017). To date, all small in-frame deletions and splice variants (the latter of which results in an inframe small duplication) have been associated with CSCFS instead of FMD2, whereas missense variants have caused both FMD2 and CSCFS (Le Goff et al 2016;Wade et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmology: He developed strabismus by age 7 years, which was initially treated with glasses, though he required surgery at age 11 and 16 years. (Sousa et al 2010;Le Goff et al 2016;Morlino et al 2018); Blue -FMD2 features from (Basart et al 2015;Wade et al 2016;Wade et al 2017;Costantini et al 2018); Green -features found in both CSCFS and FMD2; Red -novel phenotype. *Not described, but pictured in said publications.…”
Section: Patient Presentationmentioning
confidence: 99%
“…CFCS is an ultrarare, autosomal dominant disorder featuring postnatal growth delay, facial dysmorphism, vertebral and carpal anomalies, and congenital heart defect (Le Goff et al, ). More recently, the concurrence of disabling functional gastrointestinal disorder, joint hypermobility, cardiac valve disease, and minor skin features pointed out the possibility that also CFCS might be considered a hereditary soft connective tissue disorder, at least in specific cases (Morlino et al, ). The apparent overlap between TAB2 haploinsufficiency and CFCS due to TAK1 abnormalities can also be inferred by the allelic nature of selected TAB2 and TAK1 ( MAP3K7) variants in the etiology of frontometaphyseal dysplasia (FMD), a skeletal dysplasia mostly characterized by hyperostosis of the torus frontalis , metaphyseal flaring, and joint contractures.…”
Section: Discussionmentioning
confidence: 99%
“…Values were derived by taking the means of fold changes of three biological replicates per time point and cardiospondylocarpofacial syndrome (CFCS), the latter recently associated with heterozygous TAK1 variants (LeGoff et al, 2016). CFCS is an ultrarare, autosomal dominant disorder featuring postnatal growth delay, facial dysmorphism, vertebral and carpal anomalies, and congenital heart defect (LeGoff et al, 2016) Morlino et al, 2018)…”
mentioning
confidence: 99%